ANALYSIS OF FACTORS RELATED TO OCCUPATIONAL STRESS ON HEALTH WORKERS DURING THE COVID-19 PANDEMIC (LITERATURE REVIEW) - Ayunda Larasati Sekarputri; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
The COVID-19 pandemic that continues to this day puts great pressure on health workers as the front line in handling COVID-19. The great pressure experienced by health workers can cause mental health problems for health workers, such as stress, anxiety, symptoms of depression, insomnia, anger, and fear. This research is a literature review. The literature used in this study uses 4 electronic databases, namely Google Scholar, Science Direct, PubMed, and ProQuest, with the keywords "Occupational Stress on Health Workers," "Job Stress on Health Workers," "coronavirus," and "COVID-19 ". The literature results found that the factors of working hours/shifts and workload are the most widely stated factors that have a significant relationship with the incidence of work stress in health workers. The conclusion in this study is that from 10 kinds of literature obtained, 2 factors are most commonly stated as factors that have a significant relationship with the incidence of stress in health workers, namely the factor of hours/shift work with the workload. Research/literature is needed using systematic review and meta-analysis.